Carta de N. B. K. Pettingill a Roberto H. Todd - Todd, Roberto H.; Pettingill, N. B. K. (My University, 1914)
Carta relacionada a la re-elección de Roberto H. Todd.
Keywords: Elections--Puerto Rico.; Elecciones--Puerto Rico.